ROOT CAUSE ANALYSIS (RCA) OF E-CATALOGUE PROCUREMENT OF MEDICINE USING E-PURCHASING IN PUBLIC HEALTH CENTER IN KLATEN REGENCY OF CENTRAL JAVA - Liana Roh Widiyani; Enade Perdana Istyastono; Nunung Priyatni (Universitas Muhammadiyah Magelang, 2023)
E-catalogue procurement of medicine is a method of electronic procurement using a particular website developed by the Government to increase the effectiveness, efficiency, and transparency of medicine procurement. In Klaten Regency, e-catalogue procurement of medicine in the Public Health Center (PHC) experiences obstacles. The study aimed to evaluate performance of e-catalogue procurement of medicine, analyze the root problem and formulate strategies to improve the performance based on the root problems. This descriptive study involved seven PHCs with data on medicine procurement in 2021. Quantitative data analysis was conducted by evaluating six performance indicators of medicine procurement. Qualitative data analysis was conducted by interviewing 17 respondents, analyzing root problems, and formulating improvement strategies The study showed that all PHCs had good medicine availability at 87.71% average, but low realization of e-catalogue procurement occurred in two PHCs. Lead time beyond the contract period occurred in two PHCs. All PHCs experienced low suitability of procurement funds and percentage of procurement through e-catalogue. Percentage of budget allocation for medicine procurement varied between 1.59% to 7.29%. Analysis of the root problem showed obstacles in human resources, mechanism of procurement, policies, system, budget, and environment aspect. It was concluded that the obstacles rooted on the lack of team role and synergy of PHC, District Pharmacy Unit, and District Health Office according to their authority, the lack of pharmaceutical industry and distributor commitments in the provision of e-catalogue medicine for PHC, and also the urgent needs of system and regulatory improvement by the Government.